Effect of exogenous potassium on photosynthesis and antioxidant enzymes of rice under iron toxicity - Gao, P. P.; Zheng, G. H.; Wu, Y. H.; Liu, P. (Russian journal of plant physiology, 2014)
A solution culture experiment was conducted to determine the effects of different potassium concentrations on the chlorophyll fluorescence and oxidation resistance of the Fe 2+ -tolerant rice ( Oryza sativa L.) genotype Xieyou 9308 and the Fe 2+ -sensitive genotype IIyou 838 exposed to 250 mg/L of Fe 2+ . The minimal fluorescence, maximum fluorescence efficiency, maximum fluorescence, and non-photochemical quenching coefficient showed no significant changes. However, the photochemical quenching coefficient increased. Under 200 mg/L K + concentration, the effects of Fe 2+ stress decreased. Compared with the control group, chlorophyll content and peroxidase, superoxide dismutase, and catalase activities decreased, whereas MDA content increased under Fe 2+ stress. Exogenous K + alleviated Fe 2+ toxicity in the test subjects compared with the control group. Overall, external K + could alleviate the toxic effects of Fe 2+ toxicity.